Strategi Penguatan Ekonomi Kreatif Usaha Pangan Bergizi Melalui Pelatihan Pemasaran Online - Dian Roshanti; Ivan Rachmawan; Biji Bintang; Elita Endah Mawarni; Hermanto, Andrik Hermanto (Jurnal Pengabdian Masyarakat (JUDIMAS), 2023)
The potential for the food industry in the target group of Alas Purwo National Park, Banyuwangi Regency is quite large and varied, but in this global era it is full of challenges and very competitive, so that small and medium industries (IKM) need the support of various parties. This community service (PPM) aims to provide education, training, and assistance in calculating food nutrition for MSME products and improving skills and expertise in marketplace-based online marketing techniques. Society in nutritional calculations and marketing. Apart from that, this activity is also expected to be able to improve the economy and understanding of science and technology for the target audience so that they are more productive in marketing. The target of dedication is 10 members of UKM Kedungsari Purwoharjo Village, Banyuwangi. Problem solving is carried out in three stages of activity, namely (1) the preparation stage, (2) the implementation stage, and (3) the stage evaluation. The approach/preparation stage is carried out by way of outreach, observation, interviews, with potential partners. The implementation phase is carried out by giving education, knowledge, and training to the community. The monitoring and evaluation stage is carried out with assistance and monitoring of Kedungsari Village UMKM members in practicing food nutrition calculations and MSME product marketing techniques. The results of this PPM activity were to show indications of success by members of the Kedungsari Village UMKM in practicing food nutrition calculations and MSME product marketing techniques by applying the knowledge that had been given and being able to improve the economy of the Kedungsari Village community so that the community became more innovative and productive. Keywords: Training, Marketing, nutritious food ]